P047 The ATG16L1 T300A polymorphism in Crohn's Disease patients leads to abnormal autophagy flux in dendritic cells. (27th May 2021) - Quiniou, G; Dinet, O; Cervantes, O; Verdet, M; Boschetti, G; Viret, C; Nancey, S; Faure, M; Rozieres, A
Abstract: Background: Crohn's disease is a chronic inflammatory bowel disease, whose pathogenesis is largely determined by an inappropriate immune response towards luminal microbiota in genetically susceptible hosts, affecting in particular genes involved in the autophagy process. The autophagy-related ATG16L1 T300A variant is one of the most frequently associated polymorphisms with susceptibility to Crohn's disease, but the functional consequences of this polymorphism on the dynamic properties of the autophagy flux remains unknown. Methods: Using dynamic monitoring of LC3 lipidation, a key protein marker of autophagy, we have quantitatively analysed the autophagic flux of human primary dendritic cells, which are very potent antigen-presenting cells whose function is critical in Crohn's disease. Results: The detailed analysis of the dynamic properties of the autophagic flux reveal that the maturation process in dendritic cells from healthy subjects is associated with a decrease of the velocity and the intensity on the autophagy flux although the turnover of autophagosome formation was maintained, demonstrating the capacity of resilience of the autophagy flux for a maintenance of functional autophagy during maturation process. Strikingly, the expression of the ATG16L1 T300A variant, but not NOD2 R702W variant, in dendritic cells from patients with Crohn's disease is associated with a disorder of the autophagic flux dynamics in immature dendritic cells, that was not modulated upon maturation. The lack of adaptation of the autophagy flux in ATG16L1 T300A expressing dendritic cells of Crohn's disease patients, during their maturation was not associated with altered phenotypic acquisition of maturation markers but highlighted a very specific autophagic flux signature. Conclusion: Dendritic cells of Crohn's patients expressing the autophagy-related ATG16L1 T300A have an altered autophagy flux, that could affect their function and contribute to the pathogenesis of Crohn's disease.